2015
DOI: 10.5901/mjss.2015.v6n5s5p157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diversification Strategy, Leverage and IOS on Multi Segment Corporate Performance in Indonesia

Abstract: This study examines the impact of diversification strategies, the level of use of debt (leverage)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…A good firm performance must support efforts to get funds from the capital market. These findings are consistent with Christiningrum (2015); Obeten et al, (2014). They found that investment opportunity set has a positive effect on firm performance.…”
Section: Investment Opportunity Set On Firm Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…A good firm performance must support efforts to get funds from the capital market. These findings are consistent with Christiningrum (2015); Obeten et al, (2014). They found that investment opportunity set has a positive effect on firm performance.…”
Section: Investment Opportunity Set On Firm Performancesupporting
confidence: 92%
“…Investment option can be used as an opportunity for a company to develop. Christiningrum (2015) also found that investment opportunity set has a positive effect on firm performance. H3: Investment opportunity set has a positive effect on firm performance Firm performance was measured by using Price Earning Ratio (PER) proxy.…”
Section: Investment Opportunity Set On Firm Performancementioning
confidence: 85%
See 1 more Smart Citation
“…Managers take advantage of REM to use accounting window dressings. Christiningrum (2020) discovered consistent findings that as debt levels rise, managers of businesses tend to use unusual cash flows, discretionary spending, and production. Similarly Mamatzakis et al (2023) LEV positively influence the REM.…”
Section: Real Based Earnings Management and Leverage Role Of Business...mentioning
confidence: 72%
“…Due to the manager's seasonal nature, these results are stronger in the year's second half. Christiningrum (2020) looked into how debt affected earnings quality simultaneously and discovered that debt level significantly positively impacts REM. LEV is employed to calculate the debt level for fictitious results, and REM is used to calculate earnings quality.…”
Section: Literature Review Earnings Management and Leveragementioning
confidence: 99%